2023
DOI: 10.3934/publichealth.2023044
|View full text |Cite
|
Sign up to set email alerts
|

Microbial infections as potential risk factors for lung cancer: Investigating the role of human papillomavirus and chlamydia pneumoniae

Emmanuel Kwateng Drokow,
Clement Yaw Effah,
Clement Agboyibor
et al.

Abstract: <abstract><sec> <title>Background</title> <p>Lung cancer is the leading cause of cancer morbidity and mortality worldwide. Apart from tobacco smoke and dietary factors, microbial infections have been reported as the third leading cause of cancers globally. Deciphering the association between microbiome and lung cancer will provide potential biomarkers and novel insight in lung cancer progression. In this current study, we performed a meta-analysis to decipher the possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…C. pneumoniae is a Gram-negative bacterium that is a common respiratory pathogen causing chronic and persistent respiratory infections [ 80 ]. Studies have shown that C. pneumoniae infection significantly increases the risk of lung cancer [ 23 , 81 , 82 , 83 , 84 ]. Although the mechanisms underlying C. pneumoniae -promoted lung cancer are still unknown, chronic inflammation caused by C. pneumoniae infection is inextricably linked to the development of lung cancer.…”
Section: Bacteria and Lung Cancermentioning
confidence: 99%
“…C. pneumoniae is a Gram-negative bacterium that is a common respiratory pathogen causing chronic and persistent respiratory infections [ 80 ]. Studies have shown that C. pneumoniae infection significantly increases the risk of lung cancer [ 23 , 81 , 82 , 83 , 84 ]. Although the mechanisms underlying C. pneumoniae -promoted lung cancer are still unknown, chronic inflammation caused by C. pneumoniae infection is inextricably linked to the development of lung cancer.…”
Section: Bacteria and Lung Cancermentioning
confidence: 99%
“…Other target proteins and genes regulated by E6/E7 are as follows: HIF-1α, VEGF, IL-6, IL-10, Mcl-1, Bcl-2, cIAP-2, EGFR, FHIT, hTERT, HER-2, ROS1, and AhR. The collective impact of these alterations generally enhances lung cell proliferation, angiogenesis, and cell immortalization [6,11,24]. In particular, hypoxia-inducible factor-1α (HIF-1α) protein accumulation and vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8) expression promotes angiogenesis [24].…”
Section: The Role Of Hpv In Lung Cancer Development 21 Hpv Genotypes ...mentioning
confidence: 99%
“…HPV-DNA was discovered not only in neoplastic lung cells [4][5][6]11,27] but also in human blood [6,11,27] and peripheral mononuclear cells [6]. The integrated form of HPV-DNA was identified in tissue samples of patients affected by NSCLC, while the episomal and mixed forms were identified in blood samples [26].…”
Section: Hpv Infection Of Lung Cells: Pathogenesis Prevalence and Car...mentioning
confidence: 99%
See 2 more Smart Citations